A SYSTEMATIC REVIEW OF RESEARCH ON THE USE OF AUGMENTED REALITY TECHNOLOGY IN EDUCATION - Tazabekova П.Қ.; Nurbekova Ж.К.; Aimicheva Г.И.; Naimanova Д.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article is devoted to a systematic review of research in the field of application of end-to-end digital technologies in education on the example of AR technologies. The use of end-to-end digital technologies involves training specialists in accordance with market requirements, generating ideas and developing digital breakthrough technologies through the introduction of international experience in the use of digital educational technologies and improving the effectiveness of professional training of teaching staff. The article touches upon one of the directions of end-to-end digital technologies related to the use of AR technologies in education. The effectiveness and necessity of the use of AR technologies in education, on the one hand, and the insufficient competence of teachers in the modeling of 3D objects for the implementation of AR technologies, the lack of ready-made solutions for 3D modeling and the use of AR technologies in Kazakh education, on the other hand, causes an objective prerequisite for research in this area. The purpose of the article is to analysis of domestic and foreign experience of using AR technologies in education.